2014
DOI: 10.1117/1.jmm.13.3.033002
|View full text |Cite
|
Sign up to set email alerts
|

Size and shape control of sub-20 nm patterns fabricated using focused electron beam-induced processing

Abstract: Abstract.In a first study to analyze the feasibility of electron beam-induced deposition (EBID) for creating certain patterns in advanced lithography, line patterns were fabricated on silicon wafers using EBID. The growth conditions were such that the growth rate is fully determined by the electron flux (the current limited growth regime). It is experimentally verified that different patterning strategies, such as serial versus parallel patterning and single pass patterning versus multiple pass patterning, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In summary, the observed edge-broadening for high primary electron energy is an unavoidable effect ultimately contributing to the finally achievable, fully-functional edge sharpness. It is important to mention that absolute values of the proximity radii strongly depend on the experimental setup as impressively demonstrated by van Oven et al and Hari et al [ 15 , 43 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In summary, the observed edge-broadening for high primary electron energy is an unavoidable effect ultimately contributing to the finally achievable, fully-functional edge sharpness. It is important to mention that absolute values of the proximity radii strongly depend on the experimental setup as impressively demonstrated by van Oven et al and Hari et al [ 15 , 43 ].…”
Section: Discussionmentioning
confidence: 90%
“…While highly accurate and reproducible surface morphologies are essential for some of these applications, e.g., nano-optics, all of these applications require predictable and reproducible shape control in the context of high integration densities due to the ongoing downscaling trends. While Hari et al recently demonstrated the fabrication of sub-20 nm structures by a careful experimental setup [ 43 ], Arnold et al described the role of backscattered electrons (BSEs) generated by the growing deposit itself and its consequences on lateral broadening effects [ 44 ]. Both studies, however, used highly defined quasi-1D or quasi-2D structures as ideal test models and/or with the aim of unique lithography alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a maskless direct-write method would be favorable in comparison to common resist-based lithography techniques, which require multiple steps and are reaching their lateral resolution limits. Focused electron beam induced deposition (FEBID) represents such an approach providing a high lateral resolution [ 1 3 ] as well as three-dimensional possibilities [ 4 5 ]. The focused electron beam of an electron microscope is used to dissociate precursor molecules in the microscope's chamber.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition occurs in the current limited regime in which there is an abundant supply of precursor molecules. Hence the resulting deposits will not be affected by the chosen writing strategy (single pass or multi-pass), as demonstrated by Hari et al [15]. The multi-pass strategy is preferred because it is less sensitive to drift.…”
Section: Nmmentioning
confidence: 79%